(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
One of the methods of reducing the construction height of the coating or overlap using glued wooden beams, as well as the connection along their length is to perform undercuts in the support nodes. The same method is used in the design of beam ceilings, where the support of secondary beams on the main ones is carried out in pre-selected sockets in both the main and secondary beams. As for the calculation of such nodes, the normative documents only provide a calculation method for the case when the support nodes are cut with a bevel, or strict restrictions are set regarding the depth of cutting a beam without a bevel on the side of the stretched zone in relation to its height. In addition, a number of regulatory documents recommend installing glued or screwed rods in the pruning area, but no data on their calculation is provided. Therefore, the aim of this research was to develop a model allowing to estimate the carrying capacity of supporting assemblies of wooden glued beams with various depths of cut according to the height of the cross- section, and reinforcements in the form of glued perpendicular to the fiber steel rods. To achieve this goal, experimental and theoretical studies of fragments of beam support units were performed using methods of fracture mechanics. Theoretical studies were performed using a program that implemented the finite element method and implemented a procedure for determining stress intensity coefficients. As a result of numerical studies, according to the proposed method based on the use of the failure criterion, the regularities of changes in the bearing capacity depending on the ratio of the depth of the inset and the diameter of the glued reinforcing rods are determined. As a result of tests of full-scale fragments of support nodes of beams with undercutting, the reliability of the accepted method of numerical research and the developed model for determining the bearing capacity of nodes was confirmed. Based on the obtained research results, it was found that the presence of undercutting in the support nodes of wooden glued beams on the side of the stretched edge significantly reduces their load – bearing capacity, and the installation of two reinforcing steel rods with a diameter of 16 mm to 20 mm glued across the wood fibers at a distance of at least three diameters from the vertical face of the undercut increases the load-bearing capacity of the node by 8 to 10 times, compared to nodes without reinforcing rods.